2011
DOI: 10.1007/s11467-011-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory calculations of the metal-doped carbon nanostructures as hydrogen storage systems under electric fields: A review

Abstract: This review covers structural, electronic, and hydrogen storage properties of carbon-based materials with doped metals under electric fields with different orientations and intensities, which are determined by density functional theory (DFT) simulations. The special application case is considered in investigating variations of electronic structures, binding, and hydrogen storage properties. External fields that are often met in practical applications lead to changes of the above properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 115 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…However, theoretical studies have shown that TM-doped CNTs improve H 2 adsorption. Yildirim et al found that Ti atoms uniformly coated on nanotube surface could adsorb ∼8 wt % of H 2 . They also report that SWCNT (12,0) doped with TM atoms such as V and Sc bound up five H 2 molecules .…”
Section: Introductionmentioning
confidence: 99%
“…However, theoretical studies have shown that TM-doped CNTs improve H 2 adsorption. Yildirim et al found that Ti atoms uniformly coated on nanotube surface could adsorb ∼8 wt % of H 2 . They also report that SWCNT (12,0) doped with TM atoms such as V and Sc bound up five H 2 molecules .…”
Section: Introductionmentioning
confidence: 99%